EKSPLORASI PERILAKU DIGITAL SISWA SEKOLAH DASAR DALAM INTERAKSI MEDIA SOSIAL MELALUI LKPD LITERASI DIGITAL DI SDN PETAONAN 2 - Fatiya Auliya; Nur Aisyah Noviyanti; Warosatul Amalia; Mujtahidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of digital technology has increased the use of social media among elementary school students. This condition requires an understanding of students' digital behavior so that the use of social media can be done wisely and responsibly. This study aims to describe students' digital behavior in the use of social media through the use of digital literacy LKPD (Student Worksheet) at SDN Petaonan 2. The research uses a descriptive qualitative approach with a case study method. The research subjects consist of teachers and students. Data collection was carried out through observation, interviews, and digital literacy LKPD in the form of open-ended questions designed to explore students' experiences, habits, and understanding in using social media. Data was analyzed using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that most students have actively used social media for communication, entertainment, and obtaining information. Through LKPD, it was found that students already have a basic understanding of the ethics of using social media, but there is still a tendency to overuse and lack of ability to filter digital content. Schools play a role through restricting the use of mobile phones and providing directions on the wise use of social media. Therefore, collaboration between schools and parents is needed in improving students' digital literacy from an early age.